Significant improvement in the photovoltaic stability of bulk heterojunction organic solar cells by the molecular level interaction of graphene oxide with a PEDOT: PSS composite hole transport layer. (June 2018) - Hilal, Muhammad; Han, Jeong In
Highlights: Effect of different HTLs on the stability and performance of organic solar cells. GO/PEDOT:PSS HTL shows an improvement in stability and PCE over bare GO or PEDOT:PSS. The improvement is due to the bond formation at the interface of GO/PEDOT:PSS HTL. The study is paving a way for a new technique to improve the stability of OSCs. Abstract: In this paper, we report on the use of molecular level interaction between a composite poly(3, 4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT: PSS) and graphene oxide (GO) hole transport layer (HTL) to improve the long term stability and performance of poly(3-hexylthiophene): poly(3-hexylthiophene): 3′H-cyclopropa [8, 25] [5, 6] fullerene-C60-D5h(6)-3′-butanoic acid 3′-phenyl methyl ester (P3HT: PCBM)-based bulk heterojunction organic solar cells (OSCs). The device employing this composite HTL demonstrated a maximum power conversion efficiency (PCE) of 4.82% with good reproducibility and retained over 30% of its initial PCE without encapsulation after 15 days under atmospheric conditions. This was a significant improvement compared with devices fabricated with either single GO or PEDOT: PSS HTLs, which retained only 26% and 0% of their initial PCE values of 3.16% and 4.00%, respectively. Hence, we imagine that this air resistant HTL composite will probably contribute significantly to the widespread commercialization of low cost and easily fabricated OSCs.